Phenotypic studies on terrestrial stigonematacean Cyanobacteria from the Atlantic Rainforest, São Paulo State, Brazil - Sant’anna, Célia L.; Kaštovský, Jan; Hentschke, Guilherme S.; Komárek, Jiří (Phytotaxa, 2013)
The terrestrial cyanobacterial microflora of the Atlantic Rainforest is very rich and particular, occurring among numerous epiphytic plant communities, but also growing on mosses, tree barks, various wooden substrates, rocks, and on soil (mainly lateritic). The diversity of terrestrial populations from the genera Fischerella (2 species) and Stigonema (7 species), collected in different tropical and subtropical zones of the Atlantic Rainforest is described in this article. One of the Fischerella morphotypes was not recognizable according to the available literature, and it was described as a new species (Fischerella clavata). Several Stigonema taxa are morphologically characterized and further data on their variability and diversity are provided. Three new species are described for the genus Stigonema (S. fremyi, S. corticola, and S. parallelum), and one is raised to species level (S. crassivaginatum).